Design of broadband microwave amplifiers with prescribed gain-frequency slopes / Prof. Madya Dr. Zaiki Awang and Mohd. Nor Md. Tan - Awang, Zaiki (Prof. Madya Dr.); Md. Tan, Mohd. Nor (2005)
A computer-aided design routine was developed using Matlab to synthesize interstage matching networks with prescribed gain-frequency slope for use in broadband microwave amplifiers; A graphical user interface (GUI) was developed within Matlab to assist the user in the design process. The GUI does not require prior knowledge of Matlab and only requires the user to enter the required design parameters. The software developed then prompts Matlab to solve polynomial equations associated with the insertion loss function of the inter-stage network defined by the user. The result obtained is given in the form of a schematic diagram of the matching network of lumped circuit elements which can then be imported to commercially available microwave design packages for circuit simulation. The GUI also allows the user to plot the insertion loss response as a function of frequency. In addition to its application in microwave amplifier design, the GUI is also capable of synthesizing matching networks of arbitrarily-defined gain-frequency slopes for other, as yet undefined, applications. The software developed is applied to the design of a two stage broadband microwave amplifier for use in the frequency range of 4 to 8 GHz. The amplifier uses NEC GaAs MESFET transistors which exhibit a gain roll-off of approximately 6dB/octave in the microwave region. The GUI was used to synthesize a matching network of 6 dB/octave slope to compensate for this roll-off. The amplifier designed exhibit a flat response over the pass-band with gain of the order of 9 ± 0.5 dB, and average in-band input and output VSWRs of 3 and 7 respectively.